Weakly linear homomorphisms in skew boolean modules - Dawit Chernet; K. Venkateswarlu (Journal of Hyperstructures)
In this paper we introduce the notion of linear, weakly linear and strongly linear homomorphisms between two Skew Boolean modules and obtain various properties. We also introduce a scalar multiplication on the set of all weakly linear homomorphisms (wHom(V, W)) and prove that (wHom(V, W)) is again a Skew Boolean module . Further We show that the set of all strongly linear homomorphisms (stHom(V, W)) is a sub Skew Boolean module of wHom(V, W).